2022
DOI: 10.1177/01447394221087885
|View full text |Cite
|
Sign up to set email alerts
|

The experience of teaching public administration in Russia during the pandemic in 2020–2021

Abstract: The main aim of the study was to analyze the impact of the Covid-19 Pandemic both on the public services and on public administration (PA) education, to find out how the process of teaching of future public administrators had changed during the Pandemic and how these changes could possibly influence the process of teaching public administrators in future. The research methods included theoretical and analytical research methods, the methodology of empirical research, and comparative research methods. The lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…However, there remains a hyper-focus on institutional needs and outcomes for their programs and students that tend to place the onerous burden of responsibility for implementation squarely on the shoulders of educators. Nurlybaeva (2023) analyzed PA education in Russia during the Covid-19 pandemic and concluded that 'digitalization of the teaching and learning process and organization of distant learning' were crucial processes in PA education and that they could also continue to be applied in the future. However, such an approach requires multiple changes on the behalf of both students and professors, as true digital competencies must be acquired by both sides, while program structures and mentalities have to adapt to the new reality.…”
Section: Effects Of the Covid-19 Pandemic On University Educatorsmentioning
confidence: 99%
“…However, there remains a hyper-focus on institutional needs and outcomes for their programs and students that tend to place the onerous burden of responsibility for implementation squarely on the shoulders of educators. Nurlybaeva (2023) analyzed PA education in Russia during the Covid-19 pandemic and concluded that 'digitalization of the teaching and learning process and organization of distant learning' were crucial processes in PA education and that they could also continue to be applied in the future. However, such an approach requires multiple changes on the behalf of both students and professors, as true digital competencies must be acquired by both sides, while program structures and mentalities have to adapt to the new reality.…”
Section: Effects Of the Covid-19 Pandemic On University Educatorsmentioning
confidence: 99%